The effects of workplace friendship network centrality on deep acting - Kim, Na Yoon; Oh, Hongseok (Frontiers in Psychology, 2023)
We integrated social network theory with conservation of resource theory to predict that workplace friendship network centrality provides service employees with critical psychological resources that foster deep acting: positive affect and positive self-perception. In Study 1, we conducted a survey (N = 105) in a Korean banking firm, revealing that these resources mediate the relationship between workplace friendship network centrality and deep acting. Studies 2 and 3, both experimental studies, investigated the hypothesized causal relationships. In Study 2 (N = 151), we found that workplace friendship network centrality increases the intention toward deep acting. Further, Study 3 (N = 140) confirmed the direct effects of friendship network centrality on positive affect and self-perception. By providing insights into the structural antecedents of emotional labor, we inform managers in service organizations of the value of creating avenues for their employees to form and maintain friendships within the organization.